Assessment of Mixed Cultivation Substrate (Burnt Husk-Sawdust-Bagasse) and NPK Fertilizer on Growth Performance of Oyster Mushroom (Pleurotus ostreatus) - Muthmainnah Muthmainnah; M. Idris (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: Oyster mushroom cultivation generally uses sawdust as the primary rowin medium. Limited availability and fluctuating prices require innovation for mushroom planting media. The use of bagasse and burnt husk waste as an alternative medium in an effort to maximize abundant but underutilized agroindustrial resources has the potential to become a medium for growing oyster mushrooms, as the cellulose and lignocellulose content can support optimal mycelium growth. Therefore, this study aims to analyze the effect of using burnt husk as planting media, bagasse, and NPK fertilizer on the growth of oyster mushrooms (Pleurotus ostreatus). Methodology: This study employed a factorial Group Random Design method, consisting of two factors: the combination factor of substrate media (M) and NPK fertilizer dosage (N). The observed parameters included mycelial growth, cap dimeter and fresh weight of the mushroom. Data were analyzed by using Analisys of Variance (ANOVA) with SPSS v.25. Findings: The results of the data analysis showed the optimization of fungal growth in a combination of 1000 gr of sawdust and 80 gr burnt husk without the addition of NPK fertilizer with f calculated > f table (7.08>3.63). The ANOVA test confirmed that NPK fertilizer did not have a significant effect on the quality of mushrooms, possibly even negatively, because NPK creates nutrient-rich conditions that favor competing microorganisms that develop faster than oyster mushrooms. The combination of burnt husk and sawdust without NPK (M1N0) resulted in the highest mycelial growth, reaching 21.3 cm, while the lowest growth was observed in the sawdust and bagasse media with the addition of NPK (15 g) (M2N1), which was 16 cm. Meanwhile, the highest cap diameter was obtained in the Sugarcane bagasse and sawdust media without NPK (M2N0), with an average value of 8 cm. In contrast, the lowest diameter was observed in the bagasse media with an NPK of 20 g (M2N2), which was 5 cm. Contribution: This research confirms that burnt husk and sugarcane bagasse substrates, without NPK fertilizer, can serve as an effective and environmentally friendly alternative medium for oyster mushroom cultivation.